Performance of stainless steel purlin in bending - Ng, Zee Sum (2006)
The results of bending test and lateral buckling test of cold formed stainless steel purlin are presented in this dissertation. Bending test was carried out by simply supporting purlin and loaded on its top flange, while lateral torsional buckling test was done by using cantilevered purlin loaded at the free end of purlin. Theoretical bending capacity of purlin was determined from BS5950 Part 5: Code of practice for design of cold formed sections. While the buckling resistance moments were obtained from BS5950 and from Design Manual for Structural Stainless Steel published by European Stainless Steel Development & Information Group. From the bending test, it was found out that the experimental moment capacities of purlin were slightly higher than the theoretical moment capacities. However, the experimental buckling resistance moments were significantly lower than design buckling resistance moments. Therefore, the bending test method was considered satisfactory, while for lateral torsional buckling test, further studies and other testing methods were needed in order to explore verify the accuracy of cantilever method used in this study.